A comparative study of instep kicking swings, ball impacts, and ball speeds in male and female football players - Rumi Iqbal Doewes; Gunathevan Elumalai; Singgih Hendarto; Pomo Warih; Adi Manshuralhudlori (Sport TK, 2022)
Article accepted. The article will be published here soon. Pending final quality checks.